A new genus of Falagriini from the Canary Islands (Coleoptera: Staphylinidae, Aleocharinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Euphorbagria gen. n., presently containing only the designated type species E. rotundicollis (Lindberg) from Tenerife, is described and distinguished from closely related falagriine genera, particularly Myrmecopora Saulcy, Falagrioma Casey, Falagria Leach and Anaulacaspis Ganglbauer. A lectotype is designated for Falagria rotundicollis Lindberg. A detailed redescription of the type species, illustrations of diagnostic characters including the genitalia and comments on distribution and bionomics are provided. Keywords Coleoptera - Staphylinidae - Aleocharinae - Falagriini - Euphorbagria - Falagria - Palaearctic - Canary Islands - taxonomy - lectotype designation - new genus. Nomenclatural Acts rotundicollis (Lindberg, 1953) (Euphorbagria), comb. n. described as Falagria (Anaulacaspis) rotundicollis Euphorbagria Assing, 1997 (Staphylinidae), gen. n.